2017
DOI: 10.1016/j.kint.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Dietary salt restriction is beneficial to the management of autosomal dominant polycystic kidney disease

Abstract: The CRISP study of polycystic kidney disease (PKD) found that urinary sodium excretion associated with the rate of total kidney volume increase. Whether sodium restriction slows the progression of Autosomal Dominant PKD (ADPKD) is not known. To evaluate this we conducted a post-hoc analysis of the HALT-PKD clinical trials of renin-angiotensin blockade in patients with ADPKD. Linear mixed models examined whether dietary sodium affected rates of total kidney volume or change in estimated glomerular filtration ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 32 publications
3
81
0
1
Order By: Relevance
“…Renal and extrarenal phenotypes of ADPKD are heterogeneous due to the varieties of PKD mutation types [13, 15, 16], modifying genetic factors [17], gender differences [18] and environmental factors [19]. Genetic, imaging, clinical, laboratory, and environmental predictors are factors that are related to determining ADPKD disease severity [20].…”
Section: Discussionmentioning
confidence: 99%
“…Renal and extrarenal phenotypes of ADPKD are heterogeneous due to the varieties of PKD mutation types [13, 15, 16], modifying genetic factors [17], gender differences [18] and environmental factors [19]. Genetic, imaging, clinical, laboratory, and environmental predictors are factors that are related to determining ADPKD disease severity [20].…”
Section: Discussionmentioning
confidence: 99%
“…The dietary salt intake of the general population of infants, toddlers and older children on a Western diet far exceeds the recommended amounts 94 . In adults with CKD, high salt intake is associated with higher blood pressure, proteinuria and progression to ESRD [95][96][97][98] . Higher sodium intake also blunts the antihypertensive and antiproteinuric effects of RAAS blockade 99,100 .…”
Section: Salt Intakementioning
confidence: 99%
“…Higher sodium intake also blunts the antihypertensive and antiproteinuric effects of RAAS blockade 99,100 . In patients with ADPKD, urinary sodium excretion correlates with kidney growth 98,101 . Moreover, in patients with later-stage ADPKD, higher urinary sodium levels (a surrogate for sodium intake) increased the risk of a composite end point of a 50% reduction in eGFR, ESRD or death 98 .…”
Section: Salt Intakementioning
confidence: 99%
See 1 more Smart Citation
“…In a recent post hoc analysis of the HALT-PKD clinical trials, dietary sodium -measured as averaged sodium excretion -showed to be associated with the rate of TKV increase but not with the rate of eGFR decline in ADPKD patients with an eGFR over 60 mL/min/1.73 m 2 . In patients with an eGFR 25-60 mL/min/1.73 m 2 averaged sodium excretion was associated with reaching a composite end point of 50% reduction of eGFR, end-stage renal disease (ESRD) or death, and with a faster rate of eGFR decline [36] . Markers of vasopressin were not studied in the HALT-PKD trials.…”
Section: Dietary Factorsmentioning
confidence: 99%